2013
DOI: 10.4236/jamp.2013.13003
|View full text |Cite
|
Sign up to set email alerts
|

Defect and Temperature Effects on Complex Quantum-Dot Cellular Automata Devices

Abstract: The authors present an analysis of the fault tolerant properties and the effects of temperature on an exclusive OR (XOR) gate and a full adder device implemented using quantum-dot cellular automata (QCA) structures. A Hubbard-type Hamiltonian and the Inter-cellular Hartree approximation have been used for modeling, and a uniform random distribution has been implemented for the simulated dot displacements within cells. We have shown characteristic features of all four possible input configurations for the XOR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…"REVOLVING DOOR" WIRE CROSSING As described earlier, previous research has shown that devices with wire crossings that use second-near-neighbor interactions are highly susceptible to thermal effects and to even the smallest fabrication irregularities, such as displacements in dot location. [13] Thus, it is imperative to find an improved method for handling wire crossings inside QCA devices. One option for implementing an isolated wire crossing in a clocked QCA device is to allow one cell to serve as a "revolving door," conveying information first in one direction and then in the other.…”
Section: Introductionmentioning
confidence: 99%
“…"REVOLVING DOOR" WIRE CROSSING As described earlier, previous research has shown that devices with wire crossings that use second-near-neighbor interactions are highly susceptible to thermal effects and to even the smallest fabrication irregularities, such as displacements in dot location. [13] Thus, it is imperative to find an improved method for handling wire crossings inside QCA devices. One option for implementing an isolated wire crossing in a clocked QCA device is to allow one cell to serve as a "revolving door," conveying information first in one direction and then in the other.…”
Section: Introductionmentioning
confidence: 99%